Transformasi Sosial di Lembaga Pendidikan dan Dampaknya pada Masyarakat - Maskuroh, Linatul (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
This research explores social transformation at MI Nurul Huda Grugu, Kecamatan Kawunganten, Kabupaten Cilacap, and its impact on the surrounding community through a qualitative approach. In this study, MI Nurul Huda Grugu serves as the primary case study subject, with various stakeholders such as teachers, administrative staff, parents, and students participating in in-depth interviews. The research findings reveal changes in education at MI Nurul Huda Grugu, including the adoption of more inclusive teaching methods, the use of educational technology, and the adaptation of teaching methods by teachers. Social inclusion has also been enhanced through the acceptance of students from diverse backgrounds. The impact of these transformations extends beyond the school environment, affecting the surrounding community. Students who receive a more inclusive and holistically oriented education are expected to make a positive contribution to the economic and social development of the community. Although these changes have had a positive impact, there are challenges in implementing them, such as teacher training to integrate technology into teaching. Open validation with stakeholders is a crucial step in ensuring the accuracy of the research findings. This research provides initial insights into the social transformation impact at MI Nurul Huda Grugu, and further research may be needed to understand the long-term effects of these changes. With a better understanding of this topic, more effective education policies can be designed to support the community as a whole.